The Influence Mechanism of Different Cash Flow Availability on R&D Investment: Evidence from China. (8th March 2022) - Wu, Xiaobo; Hua, Ye; Lu, Hao
Abstract : It has been widely assumed and proven that a firm's research and development (R&D) investment is limited if the availability of cash flow is constrained. The purpose of this study is to verify the opposite proposition: whether firms invest heavily in R&D when more cash flow is available. This paper discusses the heterogeneous relationship between cash flow from different sources and the R&D investment of firms. The study divides the firm's cash flow into three categories according to the business activities that generate firm finance: cash flow from operating activities (CFO), cash flow from investing activities (CFI), and cash flow from financing activities (CFF). On this basis, a dynamic R&D investment model is constructed, and the relevant data for Chinese listed firms are used for the empirical research. The study finds that Chinese listed firms do not necessarily spend more cash on R&D investment, even if the availability of cash flow is not constrained. For young firms, CFO and CFI do not significantly correlate with R&D investment, and CFF significantly negatively correlates with R&D investment. For mature firms, the correlations between cash flow generated from different activities and R&D investment are nonsignificant.